'A voice for the last and least': Thirumavalavan and the Viduthalai Chiruthaigal Katchi in the Lok Sabha. Issue 1 (2nd January 2019) - Gorringe, Hugo
ABSTRACT: Between 2009 and 2014, Thirumavalavan, the leader of the largest Dalit party in Tamil Nadu, served as an MP in Delhi. This paper draws on research with the Viduthalai Chiruthaigal Katchi (VCK or Liberation Panther Party) to raise a number of key questions about representation and democracy in a multi-level federal system. Although they are a minor party, their experience of national politics offers insights into the workings of party systems in India. The paper considers the extent to which they are constrained by alliance partners and political rules-of-the-game. It then considers the question of representation, and asks what the VCK managed to achieve in Thirumavalavan's constituency of Chidambaram and the extent to which they could raise issues at the national level both through formal and disruptive means. Finally, the paper reflects on the advantages and disadvantages for a small party of having a foothold in the Centre and draws out the lessons of the VCK's experience for our understanding of Indian politics.